Alienation Occurred in “Melancholia” Movie - Irene Rosalina (STAI Nurul Islam Mojokerto, 2022)
A movie may mirror a person's experiences in life and is not just for amusement. Movies include moral lessons that viewers may learn from. It educates us about attitudes, behaviors, language, culture, and culture. It's simple for individuals to appreciate movies visually as literary. Melancholy is appropriately examined utilizing the alienation idea based on the movie's plot. Human alienation was at first a social phenomenon in contemporary life (Darma, 1995 in Efendi, 2005). Social psychology refers to this as alienation. According to Melville's 1996 short story